Propuesta, desarrollo y evaluación de un mecanismo estáticamente autobalanceado para el brazo (2018)
The problem to be solved throughout the development of this study has as a target Spastic Cerebral Paralysis patients affecting one body limb. This disability causes a lack of independence in the performance of Activities of Daily Living such as eating. One approach in solving the problem is to develop a statically balanced mechanism for assisting the weak limb so, the purpose of design is a four-link parallelogram mechanism to assist an arm movement in two degrees of freedom controlled by two angles, and . The mechanism is anchored to a pivot on a chair and connected to a weak human forearm, supported by two springs which are the actuator components that generate tensions responsible of the equilibrium.